Structural interrogation of benzosuberene-based inhibitors of tubulin polymerization. Issue 24 (15th December 2015) - Herdman, Christine A.; Devkota, Laxman; Lin, Chen-Ming; Niu, Haichan; Strecker, Tracy E.; Lopez, Ramona; Liu, Li; George, Clinton S.; Tanpure, Rajendra P.; Hamel, Ernest; Chaplin, David J.; Mason, Ralph P.; et al.
Graphical abstract: Abstract: The discovery of 3-methoxy-9-(3′, 4′, 5′-trimethoxyphenyl)-6, 7-dihydro-5 H -benzo[7]annulen-4-ol (a benzosuberene-based analogue referred to asKGP18 ) was originally inspired by the natural products colchicine and combretastatin A-4 (CA4 ). The relative structural simplicity and ease of synthesis ofKGP18, coupled with its potent biological activity as an inhibitor of tubulin polymerization and its cytotoxicity (in vitro) against human cancer cell lines, has resulted in studies focused on new analogue design and synthesis. Our goal was to probe the relationship of structure to function in this class of anticancer agents. A series of twenty-two new benzosuberene-based analogues ofKGP18 was designed and synthesized. These compounds vary in their methoxylation pattern and separately incorporate trifluoromethyl groups around the pendant aryl ring for the evaluation of the effect of functional group modifications on the fused six-membered aromatic ring. In addition, the 8, 9-saturated congener ofKGP18 has been synthesized to assess the necessity of unsaturation at the carbon atom bearing the pendant aryl ring. Six of the molecules from this benzosuberene-series of compounds were active (IC50 < 5 μM) as inhibitors of tubulin polymerization while four analogues were comparable (IC50 approximately 1 μM) in their tubulin inhibitory activity toCA4 andKGP18 . The potency of a bis-trifluoromethyl analogue74 and the unsaturatedKGP18 derivative73 as inhibitors of tubulin assembly along with their moderate cytotoxicity suggested the potential utility of these compounds as vascular disrupting agents (VDAs) to selectively target microvessels feeding tumors. Accordingly, water-soluble and DMSO-soluble phosphate prodrug salts of each were synthesized for preliminary in vivo studies to assess their potential efficacy as VDAs.